LANGUAGE POLICIES IN NEW SPAIN AND ITS IMPACT ON THE LEARNING OF INDIGENOUS LANGUAGES BY CATHOLIC MISSIONARIES - de la Cruz, Delfina; Zhizhko, Elena (Studies in Comparative Education, 2022)
This article presents the results of the historical-pedagogical study, which objective was to determine what kind of language policies was promoted in New Spain and what their impact was on the learning of indigenous languages by Catholic missionaries whose work was to evangelize indigenous peoples. The study was carried out using the documentary-bibliographic research method. The authors have found that the requirements of the Spanish Crown regarding the need for the learning and use of Amerindian languages by the conquerors vary from the recommendations not only of their acquisition but also the insistence on the creation of their grammars and vocabularies in the first stage of the conquest, until the outright prohibition of its use in the Colony in the later stages. Likewise, at various times in the development of the New Spanish language policy in the 16th century, Nahuatl had the same status as the official language (general and franca) on a par with Castilian, and it is to be assumed that under certain circumstances it could become the language of general use in the Colony. This fact indicates the importance of the work of Catholic missionaries to learn Nahuatl (and other American languages), elaborate the Nahuatl-Castilian and Castilian-Nahuatl vocabularies, and create the grammars of these languages, as well as compose the ecclesiastical texts in them. Nevertheless, the highly fickle and inconsistent language policies for New Spain, upheld by the Spanish Crown and ecclesiastical authorities, have had little influence on the issue of indigenous language learning by friars (and other colonizers). They all the time continued to learn these languages (sometimes with the support of the commanders and at other times without their consent). Therefore, the language policies promoted in New Spain did not have an imperative impact on the interpretation of the doctrinal texts of the indigenous languages by Catholic missionaries. They composed the texts (dictionaries, grammars, sermons, catechisms, confessionals) of an invaluable amount helping the preservation of the original cultures of the American continent, inciting a true fusion of two cultures, creating the hybrid philosophical-cultural field in New Spain